(untitled) - Samuelson, Paul Anthony (New York, 1995)
The book provides the microeconomic concepts such as scarcity, efficiency, the balancing of marginal costs with marginal benefits, the gains to trade, and the principle of comparative advantage. And then, it presents macroeconomics, a firm grounding in the notion of aggregate supply and demand, the role of national and international monies, the debate between Keynesian and classical economists of traditional and modern varieties
Keywords: Economics